The ethics of climate change : an introduction - Williston, Byron 1965- (Abingdon, Oxon ; New York : Routledge, 2024)
"The Ethics of Climate Change: An Introduction systematically and comprehensively examines the ethical issues surrounding arguably the greatest threat now facing humanity. This second edition has been updated and includes two new chapters on climate change and capitalism and climate change and law. Williston addresses important questions such as: Has humanity entered the Anthropocene epoch? Is climate change primarily an ethical or an economic issue? Can capitalism be reformed to prevent climate catastrophe? What are the moral failings of international climate diplomacy? What are the main causes of political inaction and climate denial? Should tort law be used to sue those responsible for climate change? What are intragenerational and intergenerational justice? Is geoengineering an ethically justifiable response to climate change? Featuring case studies throughout, this textbook provides a philosophical introduction to an immensely topical issue studied by students within the fields of applied ethics, global justice, sustainability, geography, and politics"--
Introduction : code red -- The basic science -- What is climate change ethics? -- Precautionary policy -- International justice -- Intergenerational justice -- Jurisprudential issues -- Nature in the Anthropocene -- Individual duties -- Climate change denial -- Geoengineering -- Capitalism and the climate crisis.
Includes bibliographical references and index.
Keywords: Environmental ethics; Climatic changes -- Moral and ethical aspects; Global environmental change -- Moral and ethical aspects